NILAI – NILAI PENDIDIKAN AKHLAQ ANAK KEPADA ORANG TUA DALAM AL-QUR’AN SURAT AL-AHQAF AYAT 15 - Munana al Qudsiyah; Kholfan Zubair Taqo Assidqi; Nurul Azizah (Universitas Wahid Hasyim Semarang, 2022)
ABSTRACTThis thesis discusses the values of moral education of children to parents in the Qur'an Surah Al-Ahqaf Verse 15. A universal phenomenon that a child is obliged to be devoted to both parents, do good to both parents both while still alive or already die. This can be realized by respecting him, nurturing him and always praying for him. The focus of this research is on the moral values of children to their parents and their implementation in the Qur'an verse 15. This study aims to determine what moral values are contained in the Qur'an letter Al-Ahqaf verse 15. Research This type of research uses a qualitative research approach using a descriptive analysis approach by using an analytical study method through a Library Research approach or library research. The method used in data processing is the tahlili method by following the discussion of commentators which include: interpretation of verses, asbabun nuzul verses, verse content. Based on the results of research in the Qur'an Surah Al-Ahqaf verse 15 there are values of moral education of children to parents which include: (1) Familiarizing children to always do good to their parents, (2) Familiarizing children to respect others parents, (3) Obeying the advice and orders of parents, (4) Familiarizing children to accept parents' conditions under any circumstances, (5) Familiarizing children to always pray for their parents. The values of children's moral education to parents contained in the Qur'an Surah Al-Ahqaf verse 15 can be applied in everyday life. Keyword : Moral Educational Values, Children to Parents, Surah Al-Ahqaf Verse 15